Correlation Analysis of Mortality and Length of Stay in Sepsis Cases Among Heart Failure Patients with Low Ejection Fraction at Dr. Saiful Anwar General Hospital, East Java, Indonesia - Pradhika Perdana Sakti; Setyasih Anjarwani; Mohammad Saifur Rohman; Indra Prasetya; Cholid Tri Tjahjono (Berkala Kedokteran, 2025)
In Indonesia, heart failure (HF) prevalence reaches 5%, contributing to over 1.8 million annual hospitalizations, accompanied by a 29% readmission rate and a 30-day mortality rate of 17%. The burden of infectious diseases, notably sepsis, further complicates the clinical landscape. Patients with sepsis residing in tropical regions often exhibit mortality rates surpassing global averages. Sepsis-associated coagulopathy (SAC) serves as a significant complication in this context. This study investigates the correlation between SAC, indicated by international normalized ratio (INR) levels, and outcomes in patients with heart failure with reduced ejection fraction (HFrEF) who develop sepsis. Utilizing a retrospective cohort approach, we analyzed medical records from Saiful Anwar Regional General Hospital, Malang, East Java, involving adult HFrEF patients who underwent INR testing. Purposive sampling was applied. Statistical analyses, including the Mann-Whitney Test, Kaplan-Meier Analysis, Log-Rank Test, Cox Proportional Hazards Regression, and Multiple Linear Regression, were conducted employing SPSS software. Results revealed a mean survival of 7.69 days in the Non-SAC group compared to 6.78 days in the SAC group, though the difference was not statistically significant (p=0.080). Notably, additional clinical complications predominantly influenced survival outcomes. This study elucidates that elevated INR levels, indicative of SAC, correlate with increased mortality and decreased survival in HFrEF patients with sepsis. Furthermore, the exacerbating effect of clinical complications on mortality highlights the imperative for early SAC detection and management of cardiovascular implications to enhance patient prognosis.